School Tracking and Mental Health - Petri Böckerman; Mika Haapanen; Christopher Jepsen; Alexandra Roulet (Center for Economic Studies and ifo Institute (CESifo), 2019)
We examine the effects of a comprehensive school reform on mental health. The reform postponed the tracking of students into vocational and academic schools from age 11 to age 16. The reform was implemented gradually across Finnish municipalities between 1972 and 1977. We use difference-in-differences variation and administrative data. Our results show that there is no discernible effect on mental health related hospitalizations on average even though the effect is precisely estimated. Heterogeneity analysis shows that, after the reform, females from highly-educated families were more likely to be hospitalized for depression.
Keywords: I12; I26; I28; 330; tracking age; comprehensive school; mental health; depression; hospitalization